Integración de la mujer a los mercados laborales urbanos en México : 1988-1994 - Estrella Valenzuela, Gabriel; Zenteno, René M. (El Colegio de México A.C., 1999)
This study analyzes the context of women's incorporation into the urban labor market in the recent history of Mexico. The comparative perspective of choosing sixteen cities for the analysis enables the authors to detect the patterns of general changes in this context as well as their diversity; the results show the following. First, with the exception of certain northern, especially border cities, the structure of urban employment showed a clear trend towards de-industrialization and the expansion of distributive and personal services. As a result, distributive services overtook manufacturing as the principal source of employment in some of the most important metropolitan areas in the country. Secondly, these changes were linked to an increase in self-employment in the majority of urban centers. The maquiladora centers in the north of the country, like those in Mérida, were the only ones that showed an improvement in the type of insertion of the working population. Thirdly, although the real income of workers rose in urban centers, this was achieved at the cost of a greater inequity in salaries and an expansion of the wage gap between men and women. Fourthly, in light of the changes observed throughout this period of growing openness in the Mexican economy to international competition, the great majority of urban centers saw a reinforcement of the tendency towards an increase in the age of women who participate in economic activity outside the home, a lessening of the traditional exclusion of the wives of household heads from the labor force, and as a result of the significant increase in female participation in male-headed households, a reduction in the differences in the probabilities of women's working according to the sex of the head of the household.